2018
DOI: 10.1016/j.ymthe.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Combined with BMP2-Modified Mesenchymal Stem Cells Promotes Calvarial Repair in an Osteolytic Model

Abstract: Repair and regeneration of inflammation-induced bone loss remains a clinical challenge. LL37, an antimicrobial peptide, plays critical roles in cell migration, cytokine production, apoptosis, and angiogenesis. Migration of stem cells to the affected site and promotion of vascularization are essential for tissue engineering therapy, including bone regeneration. However, it is largely unknown whether LL37 affects mesenchymal stem cell (MSC) behavior and bone morphogenetic protein 2 (BMP2)-mediated bone repair du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…The early step of bone formation involves the migration of mesenchymal stem cells (MSC), which undergo proliferation and differentiation along the osteoblastic lineage. Indeed, MSC implantation has emerged as a promising strategy for promoting bone regeneration in several clinical conditions, including delayed unions and non-unions, critical-sized bone defects, periprosthetic osteolysis, osteonecrosis, and inflammatory bone disorders [6][7][8][9][10]. The benefits of MSC therapy are mainly attributed to paracrine effects via soluble factors, exerting both immunoregulatory and regenerative actions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The early step of bone formation involves the migration of mesenchymal stem cells (MSC), which undergo proliferation and differentiation along the osteoblastic lineage. Indeed, MSC implantation has emerged as a promising strategy for promoting bone regeneration in several clinical conditions, including delayed unions and non-unions, critical-sized bone defects, periprosthetic osteolysis, osteonecrosis, and inflammatory bone disorders [6][7][8][9][10]. The benefits of MSC therapy are mainly attributed to paracrine effects via soluble factors, exerting both immunoregulatory and regenerative actions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a dual approach is mandatory to comprehend the task of hosts' immunity in response to, against periodontitis [37]. This involves more comprehensive statistics about HNP and hBD, LL-37, and other oral antimicrobial peptides and proteins, along with their mode of action and clinical significance [38][39][40][41][42][43][44][45][46][47][48][49][50]. These peptides are peculiar in keeping the level of bacteria in control, having distinctive as well as dual roles in maintaining oral health.…”
Section: Discussionmentioning
confidence: 99%
“…[175,207] In line with these findings, it was found that LL-37 can restore LPS-induced bone loss in vivo. [208] Moreover, LL-37 is thought to stabilize the defective functions of neutrophils that normally are observed around the biomaterial. [28,89] In view of the "frustrated" inflammatory state around the biomaterial, [27] there is evidence to support that LL-37 favors the differentiation of macrophages toward a wound healing and prorepair phenotype, [100,209] without impairing their ability to perform antimicrobial functions ( Figure 3B).…”
Section: Ll-37 and Derived Peptidesmentioning
confidence: 99%
“…[199] The immunomodulation by LL-37 could also promote the required macrophage-osteoblast crosstalk around the biomaterial needed for osseointegration. [208,210,211] This is a combinatorial advantage of LL-37 that could further imply its use to improve the functionality of orthopedic implants.…”
Section: Ll-37 and Derived Peptidesmentioning
confidence: 99%